Financial inclusion and women's economic empowerment: Evidence from Ethiopia - Abreham Adera; Lamessa Tariku Abdisa (Cogent Economics & Finance, 2023)
This study examines the relationship between financial inclusion and women's economic empowerment in the Ethiopian context. Scholars and development agents have long argued for the importance of access to financial products and services in achieving equitable economic growth and reducing poverty, particularly focusing on women. However, there is a limited understanding of how financial inclusion specifically impacts women's economic empowerment in Ethiopia, and little evidence regarding the determinants of women's financial inclusion within the country. This study attempts to address these research gaps. The empirical methods employed in this study include endogenous switching regression and instrumental variable methods. The data used in this study is from the Women's module of the Ethiopian Demographic and Health Survey (DHS). The findings reveal a positive and statistically significant impact of financial inclusion on women's economic empowerment in Ethiopia, indicating that greater access to financial services contributes to improved economic outcomes for women. These findings underscore the importance of collaboration between financial institutions, development agents, and policymakers to implement effective financial inclusion initiatives tailored to the Ethiopian context. Additionally, rigorous evaluation of these interventions is crucial to understand their specific effects and to ensure their successful implementation. By focusing on the Ethiopian case, this study contributes to our understanding of the relationship between financial inclusion and women's economic empowerment in the country. The findings highlight the significance of prioritizing financial inclusion strategies in Ethiopia to advance gender equality, foster economic growth, and alleviate poverty.
Keywords: 330; bargaining power; Ethiopia; financial inclusion; women's economic empowerment